Social marketing's role in improving water quality on the Great Barrier Reef. Issue 5 (11th November 2019) - Hay, Rachel; Eagle, Lynne; Saleem, Muhammad Abid
Abstract : Purpose: The purpose of this paper is to focus on the implications of claimed detrimental impacts for the agricultural activity of the Great Barrier Reef (GBR) ecosystem health in Queensland, Australia. The authors discuss the complex interaction of factors that have contributed to the decline in reef ecosystems and the challenges presented by multiple industries operating within the GBR catchment area. The authors then discuss measures employed to address agricultural run-off, claimed to be a significant factor in declining reef water quality. Design/methodology/approach: Surveys of land managers were undertaken in partnership with two of the six natural resource management (NRM) organizations operating in areas adjacent to the GBR identified as having very high risk of natural and anthropogenic runoff. The sample population was obtained from a membership database within the two regions. Participants include land managers from the both regions who engaged in sugar cane production (Region 1 and Region 2, included in this paper) and cattle production (Region 2, to be reported later). Quantitative and qualitative data were analyzed including open-ended responses. Findings: A large-scale study of land managers reveals several reasons for the lack of success at reducing agricultural run-off. The authors discuss the rationale for a move to a theory-grounded social marketing approach to encouraging land manager behavior change, highlighting barriers, and potential enablers of sustained behavior change. Originality/value: This study is first of its kind that discusses the behavior of land managers in the GBR catchment area and highlights facilitators and impediments of land managers' behavior change toward GBR protection actions.